Aktivitas Enzim Tanin Asil Hidrolase pada Kondisi Optimum Fermentasi Lactobacillus plantarum Menggunakan Tepung Ganyong (Canna edulis Kerr) sebagai Substrat - Azor Yulianus Tefa; Marselina Theresia Djue Tea (Savana Cendana, 2022)
This study aimed to determine the activity of tannin acyl hydrolase enzyme produced under the optimum conditions of Lactobacillus plantarum fermentation using canna flour (Canna edulis Kerr) flour as substrate. The research process began with the production of tannin acyl hydrolase enzyme, then proceeded with the isolation of the crude enzyme and then the activity of the tannin acyl hydrolase enzyme were measured. The variations of inoculum volume in this study were 1 mL, 3 mL, and 5 mL, with 2 grams of substrate. The variation of pH used when testing the enzyme activity was pH 4, pH 5, pH 6, and pH 7, the temperature variations used were 35°C, 40°C, 45°C, and 50°C, while the incubation time variations were 12 hours, 24 hours, 36 hours, and 48 hours. The results showed that the highest activity of tannin acyl hydrolase enzyme was obtained at 1.13 U/mL at optimum pH of 6, 0.88 U/mL at optimum temperature of 45°C, and 0.89 U/mL for optimum incubation time of 36 hours.